How should we define a nociceptor in the gut-brain axis? - Spencer, Nick J.; Hibberd, Tim; Xie, Zili; Hu, Hongzhen (Frontiers in Neuroscience, 2022)
In the past few years, there has been extraordinary interest in how the gut communicates with the brain. This is because substantial and gathering data has emerged to suggest that sensory nerve pathways between the gut and brain may contribute much more widely in heath and disease, than was originally presumed. In the skin, the different types of sensory nerve endings have been thoroughly characterised, including the morphology of different nerve endings and the sensory modalities they encode. This knowledge is lacking for most types of visceral afferents, particularly spinal afferents that innervate abdominal organs, like the gut. In fact, only recently have the nerve endings of spinal afferents in any visceral organ been identified. What is clear is that spinal afferents play the major role in pain perception from the gut to the brain. Perhaps surprisingly, the majority of spinal afferent nerve endings in the gut express the ion channel TRPV1, which is often considered to be a marker of “nociceptive” neurons. And, a majority of gut-projecting spinal afferent neurons expressing TRPV1 are activated at low thresholds, in the “normal” physiological range, well below the normal threshold for detection of painful sensations. This introduces a major conundrum regarding visceral nociception. How should we define a “nociceptor” in the gut? We discuss the notion that nociception from the gut wall maybe a process encrypted into multiple different morphological types of spinal afferent nerve ending, rather than a single class of sensory ending, like free-endings, suggested to underlie nociception in skin.